Efficient conversion of used palm cooking oil into biogasoline over hydrothermally prepared sulfated mesoporous silica loaded with NiMo catalyst - Karna Wijaya; Saffana Ramadhani; Aldino Javier Saviola; Niko Prasetyo; Saharman Gea; Latifah Hauli; Amalia Kurnia Amin; Wahyu Dita Saputri; Dita Adi Saputra; Nono Darsono (Results in Engineering)
Fossil-based fuels remain a primary global energy source, but their finite and non-renewable nature raises concerns about long-term sustainability. These issues underscore the urgent need for renewable and eco-friendly alternatives such as converting vegetable oil into biofuel. The present work reported biogasoline production from used palm cooking oil catalyzed by sulfated mesoporous silica impregnated with nickel-molybdenum bimetal using the hydrothermal method for both steps. We evaluated the effect of sulfuric acid concentration and metal loading amount on the acidity of the resulting catalysts. Catalysts' performance was assessed through the catalytic cracking and hydrocracking processes with a catalyst-to-feed ratio of 1 % at 550 °C and an atmospheric pressure. In comparison to mesoporous silica (MS) and sulfated mesoporous silica (SMS-2), along with an increase in acidity, NiMo-impregnated mesoporous silica (NiMo 1/SMS-2) exhibited superior catalytic performance in biogasoline production in the presence of H2 gas, achieving liquid product conversion and gasoline selectivity of 55.9 % and 52.37 %, respectively. These results are an excellent step for developing biogasoline in a safer process and confirm the capability of mesoporous silica-based catalysts in biofuel production.